Haba criolla Canavalia ensiformis (Fabaceae faboideae) - Bernal, H.Y.; Jimenéz, L.C. (Barcelona (España))
Resumen (Es)
Keywords: CANAVALIA ENSIFORMIS; FABACEAE; PAPILIONOIDEAE; BOTANICA; CITOLOGIA; TAXONOMIA; MORFOLOGIA VEGETAL; USOS; ABONO VERDE; QUIMICA; FLORACION; GERMINACION; SUELOS; COSECHA; NODULACION; PLAGAS DE PLANTAS; VIROSIS; POTENCIAL; INDUSTRIA